2023
DOI: 10.3389/fvets.2023.1143649
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lingzhi culture enhance growth performance via improvement of antioxidant activity and gut probiotic proliferation in Sanhuang broilers

Abstract: IntroductionThe experiment was conducted to evaluate the effects of Ganoderma lingzhi culture (GLC) as a fermented feed on growth performance, serum biochemical profile, meat quality, and intestinal morphology and microbiota in Sanhuang broilers. In addition, the association between gut bacteria and metabolites was investigated via untargeted metabolomic analysis.MethodsA total of 192 Sanhuang broilers (112 days old) with an initial body weight of 1.62 ± 0.19 kg were randomly allocated to four treatments, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…From the perspective of microflora structures, although the addition of UAP or FAP in the diet did not significantly affect the richness of cecum microflora, there was a tendency to increase the diversity of microflora, which was reflected by the increase in Shannon and Simpson indexes. Greater microbial diversity is associated with enhanced productivity, robust ecological communities, and heightened resistance to invasive species, thereby facilitating more efficient dietary utilization [ 54 ]. The results of β diversity in our study revealed significant differences in the microflora structures of the UAP and FAP groups compared to the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of microflora structures, although the addition of UAP or FAP in the diet did not significantly affect the richness of cecum microflora, there was a tendency to increase the diversity of microflora, which was reflected by the increase in Shannon and Simpson indexes. Greater microbial diversity is associated with enhanced productivity, robust ecological communities, and heightened resistance to invasive species, thereby facilitating more efficient dietary utilization [ 54 ]. The results of β diversity in our study revealed significant differences in the microflora structures of the UAP and FAP groups compared to the CON group.…”
Section: Discussionmentioning
confidence: 99%